2019
DOI: 10.7554/elife.46500
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional insights into the bona fide catalytic state of Streptococcus pyogenes Cas9 HNH nuclease domain

Abstract: The CRISPR-associated endonuclease Cas9 from Streptococcus pyogenes (SpyCas9), along with a programmable single-guide RNA (sgRNA), has been exploited as a significant genome-editing tool. Despite the recent advances in determining the SpyCas9 structures and DNA cleavage mechanism, the cleavage-competent conformation of the catalytic HNH nuclease domain of SpyCas9 remains largely elusive and debatable. By integrating computational and experimental approaches, we unveiled and validated the activated Cas9-sgRNA-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 68 publications
(133 reference statements)
3
38
0
Order By: Relevance
“…The pairwise GB model of Hawkins, Cramer, and Truhlar (GB HCT ) was used, adopting the parameters developed by Tsui and Case ( 49 ). Other parameters were set following our previous studies ( 46 ). For the bulge-free systems, the last 50 ns of the replicated trajectories were aggregated for calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pairwise GB model of Hawkins, Cramer, and Truhlar (GB HCT ) was used, adopting the parameters developed by Tsui and Case ( 49 ). Other parameters were set following our previous studies ( 46 ). For the bulge-free systems, the last 50 ns of the replicated trajectories were aggregated for calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The TGG PAM-containing system was subjected to a sequence of steps to reach stability following our previous protocol (46), involving thorough energy minimization and slow heating to 310.15 K followed by 50-ns equilibration. The equilibrated system was used as the starting point for the TAG and TCGG PAM systems as well as the bulge system with a canonical TGG PAM (see below).…”
Section: Quantification Of Indel Formation By Next-generation Sequencingmentioning
confidence: 99%
“…Either D 10 A [58] or H 983 A [65] mutation destroyed the RuvC nuclease activity. On the other hand, D 839 A [66], H 840 A [58], and N 863 A [67] mutations could eliminate the HNH nuclease activity. These mutations did not influence the target site binding affinity of Cas9-sgRNA.…”
Section: Crispr/cas Nucleasesmentioning
confidence: 99%
“…Here, DNA unwinding may be the key factor for Cas9 activity (Gong et al, 2018). Structures of Cas9 have also revealed that the HNH domain is mobile Nishimasu et al, 2015Nishimasu et al, , 2014bZhu et al, 2019;Zuo et al, 2019), and the catalytic conformation is preferentially adopted when Cas9 is bound to a target with perfect complementarity al., 2015) ( Figure 2.6D, E). Movement of the HNH domain also allosterically regulates cleavage by the RuvC domain, ensuring high-fidelity cleavage for both strands .…”
Section: Target Recognition and Bindingmentioning
confidence: 99%
“…Cas9 cleavage of the target strand (TS) and non-target strand (NTS) is mediated by the metal ion-dependent HNH and RuvC endonuclease domains, respectively (Gasiunas et al, 2012;Martin Jinek et al, 2012;Zuo et al, 2019) (Figure 2.6E). Recent high-resolution cryo-EM structures of Cas9 reveal three states in the pre-and post-catalysis stages (Zhu et al, 2019).…”
Section: Dna Target Cleavagementioning
confidence: 99%